2020
DOI: 10.1016/j.quaint.2019.02.029
|View full text |Cite
|
Sign up to set email alerts
|

Combined US-ESR dating of fossil teeth from El Harhoura 2 cave (Morocco): New data about the end of the MSA in Temara region

Abstract: The study of the Middle Stone Age (MSA) in North Africa is essential to better understand the human dispersals during the Late Pleistocene. The timing of the transition from the MSA to the Later Stone Age (LSA) in the region is still debated due to the scarcity of sites and the limited chronological constraints available. Among the few existing MIS 5 to MIS 1 archaeological sites in Northwestern Africa, El Harhoura 2 cave (Morocco) has been extensively excavated during the last decade. It has provided MSA and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 38 publications
0
13
1
Order By: Relevance
“…Moreover, they appear to be relevant indicators palaeo-environmental transitions and offer a range of opportunities to explore the impact of environmental changes on extinct organisms. used in this study (Stoetzel, 2009;Janati-Idrissi et al, 2012;Stoetzel et al, 2012a;Ben Arous et al, 2019, 2020. Three datations muscle (MP) from mandible shape.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, they appear to be relevant indicators palaeo-environmental transitions and offer a range of opportunities to explore the impact of environmental changes on extinct organisms. used in this study (Stoetzel, 2009;Janati-Idrissi et al, 2012;Stoetzel et al, 2012a;Ben Arous et al, 2019, 2020. Three datations muscle (MP) from mandible shape.…”
Section: Discussionmentioning
confidence: 99%
“…From top to bottom, the stratigraphy of EH2 cave is structured in 11 layers. Eight of these levels are well dated and were included in this study (L1, L2, L3, L4a, L5, L6, L7, L8) Ben Arous et al, 2019, 2020. Palaeo-environmental data were deduced from faunal communities (Stoetzel, 2009;Stoetzel et al, 2011Stoetzel et al, , 2012bStoetzel et al, ,a, 2014.…”
Section: El Harhoura 2 Cave and Data Collectionmentioning
confidence: 99%
“…Grün [42] showed that for teeth from cave sites, p en /p den ≅ 1.0 ± 0.5 was true for most teeth, while in open air sites, p en / p den ≅ 1.0 ± 1.0 for most teeth with p < 2. While combined dating was not performed on the teeth in Table 4, p values for enamel and dentine have been published in multiple studies [e.g., [43][44][45][46][47][48][49] and can serve as a proxy for the importance of this parameter. With the exception of Payre [49], all of the ones quoted come from caves.…”
Section: Another Suggestionmentioning
confidence: 99%
“…As a result, paleolandscapes of the Late Pleistocene are described as open steppe or savanna-like lands with patches of shrubs, woodlands and water bodies, the latter expanding during All of the eight studied layers have been dated (Ben Arous et al, 2020b). Three different methods were used: OSL (Optical Stimulated Luminescence) (Jacobs and Roberts, 2012;Jacobs et al, 2012), combined US-ESR (combination of uranium series and electron spin resonance methods) (Janati-Idrissi et al, 2012;Ben Arous et al, 2020a) and AMS-14 C (radiocarbon dating) (Nespoulet and El Hajraoui, 85 2012; Marquer et al, in press). However, important discrepancies appear between methods when applied to a same layer, as for the L3 dated at approximately 40 ka using combined US-ESR and at 60 ka using OSL (Fig1).…”
mentioning
confidence: 99%